Psychological distress and psychiatric disorder after natural disasters: systematic review and meta-analysis. (10th October 2018) - Beaglehole, Ben; Mulder, Roger T.; Frampton, Chris M.; Boden, Joseph M.; Newton-Howes, Giles; Bell, Caroline J.
Abstract : Background: Natural disasters are increasing in frequency and severity. They cause widespread hardship and are associated with detrimental effects on mental health. Aims: Our aim is to provide the best estimate of the effects of natural disasters on mental health through a systematic review and meta-analysis of the rates of psychological distress and psychiatric disorder after natural disasters. Method: This systematic review and meta-analysis is limited to studies that met predetermined quality criteria. We required included studies to make comparisons with pre-disaster or non-disaster exposed controls, and sample representative populations. Key studies were identified through a comprehensive search of PubMed, EMBASE and PsycINFO from 1980 to 3 March 2017. Random effects meta-analyses were performed for studies that reported key outcomes with appropriate statistics. Results: Forty-one studies were identified by the literature search, of which 27 contributed to the meta-analyses. Continuous measures of psychological distress were increased after natural disasters (combined standardised mean difference 0.63, 95% CI 0.27–0.98, P = 0.005). Psychiatric disorders were also increased (combined odds ratio 1.84, 95% CI 1.43–2.38, P < 0.001). Rates of post-traumatic stress disorder and depression were significantly increased after disasters. Findings for anxiety and alcohol misuse/dependence were not significant. High rates of heterogeneity suggest that disaster-specific factors and, to a lesser degree, methodological factors contribute to the variance between studies. Conclusions: Increased rates of psychological distress and psychiatric disorders follow natural disasters. High levels of heterogeneity between studies suggest that disaster variables and post-disaster response have the potential to mitigate adverse effects. Declaration of interest: None.